Melt- and fluid-inclusions studies in the Wunugetushan porphyry Cu–Mo deposit, NE China: Constraints on the separation of Cu and Mo - Lu, Wei; Zhang, Yuecheng; Du, Jingguo; Song, Zhiwei (Frontiers in Earth Science, 2023)
The Wunugetushan large porphyry Cu–Mo deposit in NE China is hosted by Mesozoic quartz monzonite porphyry and has a Mo-rich core and Cu-rich rim in space. In this paper melt inclusions in porphyry intrusions and fluid inclusions in different-stage quartz veins were studied to explore potential parameters leading to Cu–Mo decoupling. Melt inclusions in porphyry intrusions have rhyolitic compositions of 71.7–85.3 wt.% SiO2, 1.9–31.3 ppm Cu and 1.7–2.6 ppm Mo. Hydrothermal activity occurred over three stages: (1) Early Mo mineralization at high temperatures (543°C–560°C) and CO2-rich fluids of intermediate salinity (11.0–17.3 wt.% NaCl equivalent), accompanied by biotitization and minor K-feldspathization; (2) Late Mo mineralization involving high-salinity (up to 77.0 wt.% NaCl equiv.) oxidized fluids at intermediate temperatures (400°C–454°C), with K-feldspathization and minor sericitization; (3) A Cu-mineralization stage with high-salinity (up to 45.6 wt.% NaCl equiv.) and CO2-barren fluids characterized by temperature peaks at 250°C–300°C and 400°C–450°C, accompanied by sericitization and illitization. Given possible variations in melt Cu/Mo ratios during magmatic activity and redox conditions, pH, fluid composition, and temperature during the hydrothermal-fluid stage led to the separation of Cu and Mo, we found that integrated parameters including increased Cu/Mo ratios in residual melt, variations in the redox state and more acidic environment of hydrothermal fluids determine spatial separation of two metals.